Changes in Oral Health Policies and Guidelines During the COVID-19 Pandemic - Jiang, Chloe Meng; Duangthip, Duangporn; Auychai, Prim; Chiba, Mirei; Folayan, Morenike Oluwatoyin; Hamama, Hamdi Hosni Hamdan; Kamnoedboon, Porawit; Lyons, Karl; Matangkasombut, Oranart; Mathu-Muju, Kavita R.; Mathur, Vijay Prakash; Mei, May Lei; et al. (Frontiers in Oral Health, 2021)
The aim of this study was to describe the changes in oral health policies and guidelines in response to the Coronavirus disease 2019 (COVID-19) pandemic in different countries and regions around the world. Information on oral health policies and guidelines from 9 countries (Canada, China including Hong Kong, Egypt, India, Japan, New Zealand, Nigeria, Switzerland and Thailand) were summarized, and sources of the information were mostly the national or regional health authorities and/or dental council/associations. The changes made to the oral health guidelines depended on the severity of the COVID-19 pandemic. This included suspension of non-emergency dental care services at the peak of the COVID-19 outbreak, and easing the restrictions on non-essential and elective dental care when the pandemic became under control. The COVID-19 risk mitigation strategies include strict adherence to infection control practices (use of hand sanitizers, facemask and maintaining social distancing), reducing the amount of aerosol production in the dental setting, and managing the quality of air in the dental treatment rooms by reducing the use of air conditioners and improving air exchange. The COVID-19 pandemic has shown a major impact on dental practice. Dental professionals are trying to adapt to the new norms, while the medium to long-term impact of COVID-19 on dentistry needs further investigation.